A short story of planet earth : - Macdougall, J. D. (John Wiley, 1996)
The book offers knowledge about the earth sciences: chemical fossils, seismic waves, a gigantic earthquake, mammalian evolution... It explains the complex interaction between the geologic and biologic aspects of our planetls history